Kinetic and thermodynamic of heterogeneously K₃PO₄/AC-catalysed transesterification via pseudo-first order mechanism and eyring-polanyi equation - Ahmad Farid, Mohammed Abdillah; Hassan, Mohd Ali; Yap, Taufiq Yun Hin; Ibrahim, Mohd Lokman; Hasan, Muhamad Yusuf; Mohd Ali, Ahmad Amiruddin; Othman, Mohd Ridzuan; Shirai, Yoshihito (Elsevier, 2018)
The use of carbon-based catalysts has drawn so much interest in biodiesel production due to improved reaction performance. However, there was lack of comprehensive studies in term of its kinetic and thermodynamic perspective. Therefore, a methodical study is essential to uncover the influence of the carbon catalyst with respect to reaction rate and yield. This study represents kinetic and thermodynamic of heterogeneously K₃PO₄/AC-catalysed transesterification. It was done correspondingly via pseudo-first order mechanism and Eyring-Polanyi equation, whereby, under the optimal reaction temperature of 333.15 K, all data have fitted satisfactorily in both models with resulted R² of 0.99, respectively. Activation energy (Ea) and Gibbs free energy (ΔG) were calculated as 34.2 kJ mol⁻¹ and −33.68 kJ mol⁻¹, indicating the reaction was exergonic and spontaneous at high temperature.